The Efficacy of Moxibustion on the Serum Levels of CXCL1 and β-EP in Patients with Rheumatoid Arthritis - Siyu Tao; Xue Wang; Chenxi Liao; Yan Xiong; Jie Tang; Nannan Jiang; Yuan Li; Xinyue Hu; Rouxian Shuai; Yueyue Wang; Ping Wu (Pain Research and Management)
Objective. This study aims to evaluate the efficacy of moxibustion on joint swelling and pain and the levels of C-X-C motif chemokine ligand 1 (CXCL1), β-endorphin (β-EP) in serum of rheumatoid arthritis (RA) patients and to investigate the anti-inflammatory and analgesic mechanism of moxibustion on improving RA. Methods. Sixty-eight patients with RA were randomly and equally classified into the control and treatment groups. The control group was treated with routine drug therapy, while the treatment group received routine drug therapy and moxibustion. Both groups were treated for eight weeks. The symptoms and laboratory indicators of RA patients were compared in the two groups before and after intervention. Results. Sixty-one patients completed the study: four patients dropped out from the treatment group and three from the control group. Trial endpoints were change (∆) in symptoms, measured by Ritchie’s articular index (RAI), swollen joint count (SJC), and laboratory indicators, measured by the level of CXCL1, β-EP, tumor necrosis factor-a (TNF-α), and interleukin-1β (IL-1β). ∆RAI, ∆SJC, ∆CXCL1, ∆β-EP, ∆TNF-α, and ∆IL-1β in the treatment group were superior to the control group (13.50 [14.50] versus 6.00 [13.00] in ∆RAI, 4.00 [3.00] versus 2.00 [4.00] in ∆SJC, 0.04 ± 0.79 ng/mL versus -0.01 ± 0.86 ng/mL in ∆CXCL1, -2.43 [5.52] pg/mg versus -0.04 [4.09] pg/mg in ∆β-EP, 3.45 [5.90] pg/mL versus 1.55 [8.29] pg/mL in ∆TNF-α, and 6.15 ± 8.65 pg/mL versus 1.28 ± 8.51 pg/mL in ∆IL-1β; all P < 0.05). Conclusion. Moxibustion can improve the joint swelling and pain symptoms in patients with RA, which may be related to the fact that moxibustion can reduce the release of inflammatory factors in patients with RA and downregulate the level of CXCL1 and increase the level of β-EP at the same time. This trial is registered with ChiCTR-IOR-17012282.